LITERARY PEDAGOGY AND STUDENTS’ CHARACTER BUILDING - Rita Inderawati (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Literature will always be there as long as there are languages. In language there are good words orally and in writing. Literature shows that there are various ways in playing words with pleasant, entertaining, and educational purposes. In terms of educating, teachers and lecturers must have pedagogical abilities because in addition to delivering or informing knowledge, they must also be able to develop the personality, mentality, and the skills of the students in an integrated manner so that they are able to deal with their problems. This paper introduces how literature and pedagogy is collaborated so that it becomes a literary pedagogy, namely the study that connects literary works with education, cognition, affection, and psychomotor of their students and their  21st century learning competency. Literary pedagogy focuses on reciprocal relationships between literary work with readers and visual symbol responses to literary works that are read. Literature works with the background of diverse stories can facilitate students to achieve their actualization by applying a set of responses as tools or instruments in analyzing literary works. This literary pedagogy study theory can eliminate the assumptions of educators in this case the teaching of language and literature at various levels of education that only good literary work can be a lesson for the changes in students' behavior towards a better direction. This assumption is reasonable when the literary learning paradigm still applies a structuralist approach where students only analyze what they have found in literary works, not outside of the literary work itself